Análise econômica da aplicação de nitrogênio e fósforo na cultura do milho no município de Paraíba do Sul, Estado do Rio de Janeiro - Costalonga Seraphim , João Basílio; Gomes, Guarany Carlos; Coelho de Alvarenga , Sônia (Revista Ceres, 2025)
The demand for food products required by an increasing population has forced countries to increase food prodution to supply their needs, Experimental research has been geared to increasing productivity, to help meet this growing demand for food. The objective of this study was to determine the most economically feasible levels of nitrogen and phosphorus for corn production in the município of Paraíba do Sul, Rio de Janeiro. The experimental data was ajusted to a quadratic function and the following equation was obtained.